Penggunaan media sosial dan peran orang tua terhadap kejadian pernikahan dini - Asnuddin Asnuddin; Asrini Mattrah (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Social media use: The role of parents' perceptions about social media impact in early marriageBackground: Early marriage is a marriage that is conducted at adolescence, the factors causing early marriage are socio-cultural factors, economic pressure, level of education, difficulty in getting a job, social media, religion and views and beliefsPurpose: To find out the influence of social media and the role of parents on the incidence of early marriageMethod: A quantitative research using descriptive analytical research method with cross sectional study design with variable use of social media with the criteria for the results